2019
DOI: 10.1002/ejic.201900284
|View full text |Cite
|
Sign up to set email alerts
|

Dumbbell‐Shaped T8‐POSS with Functional Organic Linkers

Abstract: New dumbbell-shaped octasilsesquioxanes (T 8 -POSS) are obtained by the condensation of organobridged silane precursors with partially condensed T 7 -triol. The synthesis based on corner-capping proceeds under mild reaction conditions (60°C in toluene) upon a nucleophilic fluoride-catalyzed condensation of the T 7 -triol with the alkoxysilyl organics. Two

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Indeed, the fluoride ion of TBAF attacks the Si atom of alkoxysilanes, forming hypervalent silicon intermediates, which increases the nucleophilicity of Si and hence the reactivity. [23][24][25][26] Here we found that the degree of silylation of layered silicate using C 8 TES was increased in the presence of TBAF for the first time. The catalytic effect of TBAF on the silylation reaction was verified with other organoalkoxysilanes, confirming the superiority of this method.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Indeed, the fluoride ion of TBAF attacks the Si atom of alkoxysilanes, forming hypervalent silicon intermediates, which increases the nucleophilicity of Si and hence the reactivity. [23][24][25][26] Here we found that the degree of silylation of layered silicate using C 8 TES was increased in the presence of TBAF for the first time. The catalytic effect of TBAF on the silylation reaction was verified with other organoalkoxysilanes, confirming the superiority of this method.…”
Section: Introductionmentioning
confidence: 78%
“…[13] Here, we discuss the reaction mechanism of the promotion of silylation by the addition of fluoride ion (TBAF) on the basis of the sol-gel reaction of alkoxysilanes catalyzed by fluoride ions (Scheme 2). [23][24][25][26] A) An XPS peak [34] due to the F 1s orbital at 687 eV, attributed to the SiÀ F bond, [35] was observed (Figure S6), indicating the formation of unidentified Si species with an SiÀ F bond; this, in turn, indicates the nucleophilic attack on the silylating agent. [36] B) It is plausible that the oxygen atom of the SiÀ OH group at the surfaces of the layers undergoes nucleophilic attack on the Si atom that has become electrophilic due to the formation of SiÀ F bonds, resulting in the formation of a hexacoordinated state with SiÀ OÀ Si.…”
Section: Effect Of the Amount Of Tbaf On The Silylation With C 8 Tes And Plausible Silylation Reaction Mechanismmentioning
confidence: 99%
“…These signals suggest that the sulfonic groups are successfully grafted to PCS-DDSQ-SO 3 H-x. 48 The chemical structure of DDSQ and PCS-DDSQ was also confirmed by 1 H, 13 C, and 29 Si NMR spectra (Figure S1). 32 As shown in Figure 2a, the broad peak around 130 ppm in PCS-DDSQ, indicating the overlap of aromatic carbons arising from DDSQ, confirms the formation of a porous network.…”
Section: Synthesis and Characterization Of Pcs-ddsq-so 3 H-xmentioning
confidence: 72%
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acsami.2c17732. Material characterization; 1 H NMR, 13 C NMR, and 29 ■ AUTHOR INFORMATION…”
Section: ■ Associated Contentmentioning
confidence: 99%
See 1 more Smart Citation